2013
DOI: 10.5120/12149-7798
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Data Security While using Third Party Auditor

Abstract: In this paper the computing resources in the form of service rather than a utilities and product are provided to users over internet. The corporate world there are huge number of client which is accessing there data and modifying the data. The cloud is a platform where the data owner remotely stores their data in cloud. The goal of cloud computing concept is to secure and protect the data which come under the property of users and security of cloud computing environment is exclusive research area into which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…It is found that this factor is a dominant factor to ensure security on cloud storage service. On the other hand, [17] provides opposite result. In [17] described the perspective of the cloud computing user.…”
Section: Research Hypothesismentioning
confidence: 92%
See 1 more Smart Citation
“…It is found that this factor is a dominant factor to ensure security on cloud storage service. On the other hand, [17] provides opposite result. In [17] described the perspective of the cloud computing user.…”
Section: Research Hypothesismentioning
confidence: 92%
“…On the other hand, [17] provides opposite result. In [17] described the perspective of the cloud computing user. Users indicate their concerns regarding the third-party auditor.…”
Section: Research Hypothesismentioning
confidence: 92%
“…The public cloud model allows user access to clouds through interfaces using main web browsers. It is based on pay per use and has enough flexibility to cater for cloud optimization demands which enable the clients of the cloud to match their operational IT budget through the reduction of capital expenditures [5]. However, cloud computing models are less secure than other cloud models due to the additional task of ensuring that all data and applications accessed on the public cloud are not exposed to malicious attacks.…”
Section: Types Of Cloudsmentioning
confidence: 99%
“…Cloud computing can also be viewed as a service oriented architecture which uses many computer components such as the Web 2 framework, peer to peer, open source, on-demand utility computing, grid computing and distributed computing [5]. In order to minimize potential trust and security issues in clouds and in enhancing cloud management, a control measure is to ensure that a proper service level agreement of cloud computing is put in place and maintained when dealing with specialized as well as outsourced cloud service providers.…”
Section: Introductionmentioning
confidence: 99%
“…This paper only focuses on detection of data violation. The algorithms and methods to ensure data integrity are discussed in [7]. In paper [8], certain degree of integrity assurance is provided by RAID technique but it operates only on binary data, takes more computation time and also the value of determinant factor is three bits long and hence needs large memory for storage.…”
Section: Introductionmentioning
confidence: 99%